Nurses' Perception on the Implementation of Nursing Care Documentation Using Electronic Medical Record: A Literature Review - Eka Handayani; Tutik Sri Hariyati (UIMA Press, 2023)
Background: The global use of Electronic Medical Records in healthcare service organizations such as hospitals is currently undertaken as a measure to enhance efficiency and safety in healthcare provision. Despite considerable attention being given to this aspect, the benefits of this technology are often not fully realized. Objectives: This research aims to examine the concept of electronic medical records about nurses' perceptions of nursing care documentation, particularly in healthcare services. Methods: The design of this research utilizes a literature review approach by collecting several articles from selected databases, including ScienceDirect and PubMed, with articles published from 2016 to 2023. An article search was conducted by using the keywords